Desires and doubts on cultural sustainability: A study from Aotearoa New Zealand - Afrin, Tahera (European Journal of Sustainable Development, 2019)
The original research project of this study was aimed to find out the components of culture and their impacts on ako (teaching-learning) within the early childhood teacher education programmes. Ethics Approval was obtained from AUT Ethics Committee. Under a socio-cultural theoretical framework, twelve lecturers from three Tertiary Education Organisations (TEOs) were interviewed. Three cohorts of student teachers from the same TEOs participated in focus groups. Using manual thematic coding, nine broad areas of cultural components were identified. These were bicultural contexts of Aotearoa, ethnicities and multi-culturalism, individual identities, cross-cultural interactions, comfort zone, female majority, socio-economic struggles, spirituality and technology. A recently developed framework for cultural sustainability (Soini and Dessein, 2016) were applied to these areas. Some of these components were identified as more inert and less dynamic, while the rest were recognised at the other end of the framework. The data and the principle findings were contextual to Aotearoa New Zealand. However, the discussion considered the overall global trends in relation to education. Keywords: Cultural diversity, cultural sustainability,